Atributos físicos e relações com matéria orgânica do solo sob diferentes sistemas de manejo na região do cerrado. - Silva, Venâncio Rodrigues (2019)
The no-till system (NTS) has been considered as one of the most modern systems of sustainable agricultural production for the Brazilian savanna, which is based on the nonrevolving soil, maintenance of residues on the soil surface and an efficient rotation system culture, which provides positive changes in physical attributes and in maintaining or increasing the organic matter content of the Oxisols that predominate in the region. The aim of this study was to evaluate changes in the physical attributes of the soil and to relate it to the organic matter of the soil in areas under different management systems. The study was conducted in a completely randomized design with four replications. The treatments consisted of four areas: 1 - NTS 5 years ago (NTS5), 2 - NTS 17 years ago (NTS17), 3 - Conventional planting system 20 years ago (CPS20) and 4 - Native forest (NF) characterized by savanna vegetation, from which four samples composed in each area were collected. Soil mechanical resistance, root penetration (RP), soil density (Sd), volumetric moisture (Vm), macroporosity (Ma), microporosity (Mi), total porosity (TP) and soil aggregation were evaluated, depths from 0 to 0.4 m, the granulometric and chemical fractionation of the soil organic matter was carried out. The conventional tillage system together with the no-tillage system showed densification in the most superficial layer, but without causing restriction to the development of the roots.The soil density was the physical attribute that correlated significantly with all the others evaluated. The no-tillage system 17 and 5 years together with the conventional no-tillage system 20 years, were the systems that presented values closer to physical attributes in relation to native forest respectively. Changes caused by management are more noticeable up to the 0.20 m layer in the systems. The conservationist and native forest systems showed a higher content of organic matter and carbon stock in the soil, providing the best stability indicators. The conventional tillage system 20 years and no-tillage systems showed equal and lower COT, COp, COam and MOL values in relation to native forest. The no-tillage systems together with the native forest predominated the humid fraction, demonstrating the effect of the conservationist system for this fraction.